2010
DOI: 10.5194/acp-10-11779-2010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SAGE II ozone of the middle and upper stratosphere for its response to a decadal-scale forcing

Abstract: Abstract.Stratospheric Aerosol and Gas Experiment (SAGE II) Version 6.2 ozone profiles are analyzed for their decadal-scale responses in the middle and upper stratosphere from September 1991 to August 2005. The profile data are averaged within twelve, 20 • -wide latitude bins from 55 • S to 55 • N and at twelve altitudes from 27.5 to 55.0 km. The separate, 14-yr data time series are analyzed using multiple linear regression (MLR) models that include seasonal, 28 and 21-month, 11-yr sinusoid, and linear trend t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…The data used for the QBO proxy come from equatorial data up to an altitude of ∼ 32 km. However, it has been shown that the frequencies at which the QBO oscillates are different at higher latitudes than at the Equator (Tung and Yang, 1994) and at higher altitudes (Remsberg and Lingenfelser, 2010). While the use of a proxy is better than simply using oscillating functions of different frequencies (since the QBO changes frequencies over time) and the use of orthogonal functions allows for the change in amplitude and phase of the response, it cannot account for the change in frequencies.…”
Section: Predictor Variablesmentioning
confidence: 99%
“…The data used for the QBO proxy come from equatorial data up to an altitude of ∼ 32 km. However, it has been shown that the frequencies at which the QBO oscillates are different at higher latitudes than at the Equator (Tung and Yang, 1994) and at higher altitudes (Remsberg and Lingenfelser, 2010). While the use of a proxy is better than simply using oscillating functions of different frequencies (since the QBO changes frequencies over time) and the use of orthogonal functions allows for the change in amplitude and phase of the response, it cannot account for the change in frequencies.…”
Section: Predictor Variablesmentioning
confidence: 99%
“…15) showed that SAGE II and HALOE solar responses (averaged between 25 • S-25 • N) are quite similar. However, it is also important to remember that both Remsberg (2008) and Remsberg and Lingenfelser (2010) use relatively short time series in their analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The N 2 O mixing ratio at 30 km from 30 • S to 30 • N was found to be no more than 2 % G. E. Nedoluha et al: The decrease in mid-stratospheric tropical ozone 4217 higher at solar minimum compared to solar maximum, and no more 4 % from 30 to 60 • N and 30 to 60 • S. Schmidt et al (2010) used the HAMMONIA general circulation and chemistry model, and found an equatorial O 3 sensitivity of ∼ 1.4 ± 0.4 % 100 −1 solar flux units (sfu), where the difference between the 1989 solar max and the 1986 solar min is 166 sfu. The study of Remsberg and Lingenfelser (2010) shows a 3 % ozone maximum-minimum response to the solar cycle at ∼ 35 km (∼ 7 hPa) from the SAGE II measurements, with results from the HALOE measurements and from model calculations showing a smaller ozone response to the solar cycle. As discussed in Hood and Soukharev (2006), NO y in the upper stratosphere is also affected by the solar cycle.…”
Section: The Solar Cycle and Linear Trend Calculationsmentioning
confidence: 99%